The oxidation of different energy sources and features of the growth of new strains of microorganisms, isolated from industrial substrates - Блайда, І. А.; Васильєва, Т. В.; Джамбек, О. А.; Джамбек, О. І.; Баклан, В. Ю. (Problems of Environmental Biotechnology, 2016)
The selection of cultivation conditions for new strains of Acidithiobacillus ferrooxidans allows significantly intensify the process of bioleaching. This approach promotes active accumulation of biomass at the stage of active growth before adding the biomass in substrates. The strains were isolated from waste dumps coal beneficiation and fly ash from coal combustion. Have been studied the growth characteristics of new strains of mesophilic Acidithiobacillus ferrooxidans (MFLv6 and MFLad5) at different energy sources – ferrous iron (FeSO4..7H2O) and sodium thiosulfate (Na2S2O3). We set the intensity of the oxidation of energy substrates investigated strains The intensity of oxidations of energy substrates by studied strains has been established. The index pH and Eh, the concentration of oxidized Fe+3 and the number of cells were parameters that are been monitored. The features of behavior both strains at cultivation with high concentration of ferrous iron, as an energy source, have been established. In particular, the existence of a critical concentration of FeSO4.7H2O, above which there is a dramatic slowdown in growth and lysis of the cells has been observed. It has been established that for maximum biomass accumulation of strains the concentration of FeSO4.7H2O as the only energy source in 12.0 g/dm3 is optimum and 44.5 g/dm3 for the most efficient leaching of metals from the studied substrates. The isolated strains differ in the growth rate and oxidation activity of energy sources – ferrous iron and thiosulfate. The obtained results suggest the existence of a correlation between the conditions of growth of the strains, their characteristics, and is a reflection a polymorphism strains.